Influence of different chelating agents on the microhardness, surface roughness, and adhesion of biodentine to root dentin - Özdemir, Aslı; Ocak, Mevlüt S. (Nihon University, School of Dentistry, 2026)
Purpose: This in vitro study evaluated the effects of different chelating agents on dentin properties influencing the adhesion of calcium silicate-based biomaterials. The effects of 9% etidronic acid and 0.2% chitosan nanoparticles on the microhardness, surface roughness, and push-out bond strength of Biodentine were assessed. Methods: Seventy-five extracted maxillary incisors were divided into three groups according to the final irrigation protocol: 9% 1-hydroxyethylidene-1,1-bisphosphonate (HEBP), 0.2% chitosan, or 0.9% saline (control). Dentin microhardness (Vickers hardness number) and surface roughness (Ra, µm) were measured before and after irrigation. For push-out testing, standardized cavities in 60 dentin discs were filled with Biodentine and stored for 24 h at 37°C and 100% humidity. Failure modes were examined under a stereomicroscope. Data were analyzed using one-way Analysis of Variance (ANOVA), Tukey Honestly Significant Difference (HSD), Kruskal-Wallis, and paired t-tests (P < 0.05). Results: All groups showed a significant reduction in microhardness (P < 0.001), with the greatest reduction observed in HEBP. Surface roughness increased significantly and was highest in HEBP (P < 0.001). Push-out bond strength was higher in HEBP than control (P < 0.01), with no difference between HEBP and chitosan (P > 0.05). Conclusion: Both agents improved Biodentine adhesion; however, chitosan caused milder dentin alterations, indicating greater potential for dentin preservation. © 2026 Nihon University School of Dentistry.
Keywords: biodentine; chitosan nanoparticles; etidronic acid; push-out bond strength; surface roughness